(untitled) (Euro-Latin American Journal of Administrative Law, 2022)
Consideration is given to the role of fiscal control bodies in the fight against corruption by analyzing the accessory sanctions imposed by the Office of the Comptroller General of the Republic of Venezuela in cases of total or partial non-observance of the selection procedure for contractors during the 2007-2014 period to show that inadequate fiscal control can be an incentive for corruption. Thus, fiscal control is studied as a necessary activity for the fight against corruption; then presents the result of the analysis of the accessory sanctions imposed in the period 2007-2014 and lists the cases of major corruption that, by 2022, do not have a formal investigation by the Office of the Comptroller General, and finally the conclusions are presented. Subsequently, tables were prepared and the data analyzed to respond to the research premise. It is concluded that Venezuela does not have a real and effective fiscal control of public procurement that avoids or minimizes acts of corruption.